Thrombolytic Property of Homoeopathic Medicine Vipera Berus 6c and Lachesis 6c on Human Blood Clot - Dr. Dhanalakshmibaskar; Dr. S. Kiruthiga (International Journal of Scientific Research in Science and Technology, 2025)
Thrombosis or intravascular blood clotting refers to coagulation of blood inside blood vessels. Normally blood does not clot in blood vessels, because of some factors like injury to blood vessels, toughened endothelial linning (e.g.; arteriosclerosis), sluggishness of blood flow (e.g.; reduced cardiac action, hypotension, low metabolic, and immobility), agglutination of RBC, and congenital absence of protein c. Major complications of thrombosis are Deep vein thrombosis, embolism (pulmonary embolism, cerebral embolism, and coronary embolism), ischemia, necrosis, and infarction. This invitro study aimed to evaluate the thrombolytic property of vipera 6c and Lachesis 6c. thrombolytic assay method used to analyse. In this study Human blood samples will be used to assess the thrombolytic property of homoeopathic medicines Lachesis 6c and vipera 6c. The peak incidence of Lachesis 6c is obtained at 250 micrograms/ml whereas the peak incidence of vipera 6c is obtained at 500 micrograms/ml. It is concluded from the study that both Lachesis 6c and vipera 6c have anti thrombolytic activity. The peak thrombolytic activity of Lachesis 6c is obtained at 250 microgram the peak thrombolytic activity of vipera 6c is obtained at 500 micrograms
Keywords: Thrombolytic property; Vipera6c; Lachesis 6c; Human Blood clots; Thrombolytic assay